(untitled) (Pulse, 2015)
3 months old boy presented with inablility to move upper limb and cries on touching the upper limb from 1 week of age. On examination reflexes were absent in upper limb but hyper reflexia was found in lower limb. Cervical and brain MRI revealed expansion of the cervical spinal canal with smoothly marginated mass within the cervical cord which is hyperintense in T1WI, T2WI and completely loses its signal intensity in FS and gradient weighted sequences. There was no diffusion restriction and appears mostly intramedullary. MRI features were consistent with intramedullary lipoma in cervical spinal cord. Pulse Vol.7 January-December 2014 p.50-52